Primary Care Informatics Response to Covid-19 Pandemic: Adaptation, Progress, and Lessons from Four Countries with High ICT Development - Liaw, Siaw-Teng; Kuziemsky, Craig; Schreiber, Richard; Jonnagaddala, Jitendra; Liyanage, Harshana; Chittalia, Aliasgar; Bahniwal, Ravninder; He, Jennifer W.; Ryan, Bridget L.; Lizotte, Daniel J.; Kueper, Jacqueline K.; Terry, Amanda L.; de Lusignan, Simon (Yearbook of Medical Informatics, 2021)
Objective: Internationally, primary care practice had to transform in response to the COVID pandemic. Informatics issues included access, privacy, and security, as well as patient concerns of equity, safety, quality, and trust. This paper describes progress and lessons learned.Methods: IMIA Primary Care Informatics Working Group members from Australia, Canada, United Kingdom and United States developed a standardised template for collection of information. The template guided a rapid literature review. We also included experiential learning from primary care and public health perspectives.Results: All countries responded rapidly. Common themes included rapid reductions then transformation to virtual visits, pausing of non-COVID related informatics projects, all against a background of non-standardized digital development and disparate territory or state regulations and guidance. Common barriers in these four and in less-resourced countries included disparities in internet access and availability including bandwidth limitations when internet access was available, initial lack of coding standards, and fears of primary care clinicians that patients were delaying care despite the availability of televisits.Conclusions: Primary care clinicians were able to respond to the COVID crisis through telehealth and electronic record enabled change. However, the lack of coordinated national strategies and regulation, assurance of financial viability, and working in silos remained limitations. The potential for primary care informatics to transform current practice was highlighted. More research is needed to confirm preliminary observations and trends noted.
Keywords: Telemedicine; Primary Health Care; health policy; public health; severe acute respiratory syndrome coronavirus 2